FINANCIAL RISK AND EARNING MANAGEMENT: EMPIRICAL EVIDENCE FROM BANKS IN ASEAN COUNTRIES - Nyayu Khalilah Putri; Mohamad Adam; Isnurhadi; Mu'izzuddin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Earnings management practices in the banking sector are critical due to their impact on financial reporting transparency and economic stability. Factors such as Non-Performing Loans (NPL), Loan Deposit Ratio (LDR), Bank Operating Costs to Operating Income Ratio (BOPO), Capital Adequacy Ratio (CAR), and Leverage (LEV) can influence managerial decisions related to profit reporting. Therefore, this study aims to identify the factors influencing earnings management practices in the banking sector, focusing on financial risk indicators. A panel data regression analysis using STATA was applied to banks across six ASEAN countries during 2019–2023. It also controlls for external variables such as bank size, inflation, and GDP.  Its results show that LDR, CAR, and LEV significantly impact earnings management. While NPL, BOPO, and bank size do not affect earning management. Additionally, macroeconomic factors like inflation and GDP affect financial reporting. The findings emphasize the importance of transparency in financial reporting to maintain public and investor trust, which is essential for the banking sector's stability. This research addresses the urgent need to detect key risk factors driving earnings manipulation, offering empirical evidence to guide regulators in strengthening governance and oversight across ASEAN banking institutions.